Methylphenidate for Mild Cognitive Impairment: An Exploratory 3-Day, Randomized, Double-Blind, Placebo-Controlled Trial - Press, Yan; Punchik, Boris; Kagan, Ella; Berzak, Alexander; Freud, Tamar; Dwolatzky, Tzvi (Frontiers in Medicine, 2021)
Background: To evaluate the efficacy, safety and tolerability of methylphenidate (MPH) for cognitive function in older patients with mild cognitive impairment (MCI). Methods: Male and female subjects aged 65 years and older with a clinical diagnosis MCI were included in an exploratory randomized, double-blind, placebo-controlled trial. Eligible subjects were assigned to either treatment with immediate-release MPH or placebo. The active compound was administered in an increasing-dose stepwise fashion, namely 10 mg MPH on day 1, 20 mg on day 2, and 30 mg on day 3. Subjects remained under observation for 4 h following drug administration and were monitored for changes in blood pressure and for adverse events. Cognitive outcome measures included the Montreal Cognitive Assessment (MoCA) and the Neurotrax Mindstreams computerized cognitive assessment battery. Results: Of 17 subjects enrolled, 15 subjects completed the study, 7 in the active MPH group and 8 in the placebo group. The average age of the participants was 76.1 ± 6.6 years and 10 (66.7%) were men. Following the final dose a significant benefit on memory (predominantly non-verbal memory) was found in the MPH group. While 12 adverse events were reported, they were all rated as mild to moderate. Conclusions: Our finding of modest beneficial effects of MPH on memory tests in older subjects with MCI in this exploratory study is of interest and should be investigated in further studies.